1994
DOI: 10.1084/jem.179.6.1835
|View full text |Cite
|
Sign up to set email alerts
|

Steroid production in the thymus: implications for thymocyte selection.

Abstract: SummaryThe mouse thymus was assessed for its ability to produce steroids. Cultured thymic non-T cells produced soluble pregnenolone and deoxycorticosterone, and immunohistochemistry demonstrated steroidogenic enzymes in radioresistant thymic epithelial cells but not in thymocytes. Inhibition of thymic corticosterone production or blockade of the ghcocorticoid receptor with RU-486 resulted in enhanced TCR-mediated, antigen-specific deletion of immature thymocytes. These data indicate that locally produced gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
229
2
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(241 citation statements)
references
References 47 publications
9
229
2
1
Order By: Relevance
“…10 GC may be secreted by TEC, which possess all the enzymes required for their biosynthesis. 8 Our data, however, suggested that GC is not the sole mediator and that TEC deliver additional, as yet unidentified signals, which participate in apoptosis of DP cells 10 (and unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…10 GC may be secreted by TEC, which possess all the enzymes required for their biosynthesis. 8 Our data, however, suggested that GC is not the sole mediator and that TEC deliver additional, as yet unidentified signals, which participate in apoptosis of DP cells 10 (and unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, removal of endogenous GC by adrenalectomy leads to hypertrophy of the thymus [18] and spleen [19]. In addition to the adrenals, we and others have identified the thymus as a site of GC production [20][21][22][23]. A physiological role of GC in T cell development and selection is implied by the observation that TCR and glucocorticoid receptor (GR) signaling demonstrate crosstalk.…”
Section: Introductionmentioning
confidence: 99%
“…The adrenal glands are the major source of GC in the body. However, different reports indicate that GC synthesis is not restricted to the adrenal glands but may also occur at other sites of the body (Noti et al, 2009), for example, the thymus (Vacchio et al, 1994), the brain (MacKenzie et al, 2000;Davies and MacKenzie, 2003) and the vascular endothelium (Takeda et al, 1994). Recently, we have characterized the intestinal epithelium as a major source of immunoregulatory GC (Cima et al, 2004;Mueller et al, 2006Mueller et al, , 2007Atanasov et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It develops through a series of genetic mutations in pluripotent stem cells in the intestinal epithelial crypts (Davies et al, 2005). Many cancer cells aberrantly overexpress cellular proteins or neo-antigens, which can be recognized by the immune system and provoke anti-tumor immune responses (van den Broek et al, 1996;Smyth et al, 2000;Shankaran et al, 2001). Also, CRC cells are often immunogenic and can stimulate the activation of tumor-specific lymphocytes (Camus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%